Whole Genome Sequencing and RNA-seq-Driven Discovery of New Targets That Affect Carotenoid Synthesis in Phaffia rhodozyma - Shi, Zhihui; He, Xiaoxian; Zhang, Hailiang; Guo, Xuena; Cheng, Yanfei; Liu, Xuelian; Wang, Zhaoyue; He, Xiuping (Frontiers in Microbiology, 2022)
Carotenoids are unsaturated compounds with terpene groups. Among them, astaxanthin has strong antioxidant properties. It is widely used in aquaculture, food, medicine and cosmetics with a broad market prospect.Phaffia rhodozyma is an important microorganism that synthesizes astaxanthin, but its wild strains have low pigment content, long growth cycle and low fermentation temperature.Therefore,it is important to research the genetic improvement of physiological and biochemical properties of P.rhodozyma. In this study, the ARTP mutagenesis technology was adopted, through the functional evolution of the carotenoid production performance, then the comparative analysis of genomics and transcriptomics of wild strain and evolved strain, the key factor GST1 gene that affects carotenoid synthesis were discovered.